ANALISIS PERAN PERANGKAT DESA DALAM PENERAPAN WEBSITE DESA PADA MASA PANDEMI COVID-19 - Kris Ari Suryandari; Anisa Utami (P3M STISIPOL Dharma Wacana Metro, 2022)
The implementation of regional autonomy is one of the ways that local governments have to develop their respective regions, because regions are given the freedom to regulate their own households, this is in accordance with Law Number 23 Article 1 Paragraph (6) of 2014. With the convergence of technology , there are many changes that are happening very fast. The rapid development of technology and information seems to have affected every line of people's lives. The more advanced technology available in the local government must be able to use it well, in order to provide good services to the community, especially the role of the Kalirejo Village apparatus, Katon District District, Pesawaran Regency. During the pandemic, the habit of communicating and interacting was replaced by meeting in cyberspace or so-called virtual and relying on the internet. The transformation of the communication method is a challenge for all levels of village society, so the role of village officials in optimizing the application of village websites, especially to improve the quality of services for the community in the midst of the Covid-19 outbreak, is very much needed. This research method is descriptive qualitative with village officials informants. The focus of the research is directed at the role of village officials in improving community services, especially in the application of village websites. The results of this study The level of knowledge of the Kalirejo Village apparatus towards understanding the role of the Village Apparatus in the Implementation of Village Websites during the Covid-19 Pandemic is quite good. This is supported by the facilities and infrastructure available at the Kalirejo Village Office which can be used to support the implementation of the village website as well as the level of awareness and behavior of the Kalirejo Village apparatus to be able to reactivate and manage the village website already towards responsive, aware and caring behavior so that they feel the need. self-capacity.